Barriers to Transforming Hostile Relations: Why Friendly Gestures Can Backfire. (February 2014) - Menon, Tanya; Sheldon, Oliver J.; Galinsky, Adam D.
Abstract Friendly gestures (e.g., smiles, flattery, favors) typically build trust and earn good will. However, we propose that people feel unsettled when enemies initiate friendly gestures. To resolve these sensemaking difficulties, people find order through superstitious reasoning about friendly enemies. Supporting this theorizing, friendly enemies created sensemaking difficulty, which in turn mediated people's tendencies to blame them for coincidental negative outcomes (Experiment 1). Further implicating these processes, individuals high in need for structure were especially prone to make these attributions (Experiment 2). Finally, we explored consequences of such blame, showing that blame mediates people's beliefs that mere contact with friendly enemies is unlucky and should be avoided (Experiment 3). Taken together, these results suggest that, rather than transforming hostile relationships, an enemy's friendliness can be so unnerving that it sometimes leads people down blind alleys of superstitious reasoning.